Appearance
❓Given that (-1), (a_{1}), (a_{2}), (8) form an arithmetic sequence, and (-1), (b_{1}), (b_{2}), (b_{3}), (-4) form a geometric sequence, find the value of ( dfrac {a_{1}a_{2}}{b_{2}}).A: (-5)B: (5)C: (- dfrac {5}{2})D: ( dfrac {5}{2})
💡Okay, so I have this problem where I need to find the value of (dfrac{a_{1}a_{2}}{b_{2}}). The problem says that (-1), (a_{1}), (a_{2}), (8) form an arithmetic sequence, and (-1), (b_{1}), (b_{2}), (b_{3}), (-4) form a geometric sequence. Hmm, okay, let me break this down step by step.First, let me recall what an arithmetic sequence is. In an arithmetic sequence, the difference between consecutive terms is constant. So, if I have four terms (-1), (a_{1}), (a_{2}), (8), the difference between each term should be the same. Let me denote this common difference as (d). So, starting from (-1), the next term is (a_{1} = -1 + d). Then, (a_{2} = a_{1} + d = (-1 + d) + d = -1 + 2d). Finally, the last term is (8 = a_{2} + d = (-1 + 2d) + d = -1 + 3d). Wait, so if (8 = -1 + 3d), I can solve for (d). Let me do that:(8 = -1 + 3d)Adding 1 to both sides:(9 = 3d)Dividing both sides by 3:(d = 3)Okay, so the common difference (d) is 3. Now, let me find (a_{1}) and (a_{2}):(a_{1} = -1 + d = -1 + 3 = 2)(a_{2} = -1 + 2d = -1 + 6 = 5)So, (a_{1} = 2) and (a_{2} = 5). That seems straightforward.Now, moving on to the geometric sequence part. The terms are (-1), (b_{1}), (b_{2}), (b_{3}), (-4). In a geometric sequence, each term is multiplied by a common ratio (r) to get the next term. So, starting from (-1), the next term is (b_{1} = -1 times r), then (b_{2} = b_{1} times r = (-1 times r) times r = -1 times r^2), and so on.Since there are five terms, the last term is (-4). Let me express the last term in terms of (r):The first term is (-1), and the fifth term is (-4). In a geometric sequence, the (n)-th term is given by (a_n = a_1 times r^{n-1}). So, the fifth term is:(-4 = -1 times r^{4})So, let me solve for (r):(-4 = -1 times r^{4})Divide both sides by (-1):(4 = r^{4})Taking the fourth root of both sides:(r = sqrt[4]{4}) or (r = -sqrt[4]{4})Hmm, but since we have an even number of terms, and the signs of the terms alternate? Wait, let me check the signs:First term: (-1)Second term: (b_{1} = -1 times r)Third term: (b_{2} = -1 times r^2)Fourth term: (b_{3} = -1 times r^3)Fifth term: (-4 = -1 times r^4)So, the fifth term is (-4), which is negative. The first term is also negative. So, the common ratio (r) must be positive because if (r) were negative, the signs would alternate. Let me verify:If (r) is positive, then:- First term: (-1)- Second term: (-1 times r) (negative)- Third term: (-1 times r^2) (negative)- Fourth term: (-1 times r^3) (negative)- Fifth term: (-1 times r^4) (negative)But the fifth term is (-4), which is negative, so that works. If (r) were negative, the terms would alternate signs:- First term: (-1)- Second term: (-1 times (-r)) (positive)- Third term: (-1 times (-r)^2) (negative)- Fourth term: (-1 times (-r)^3) (positive)- Fifth term: (-1 times (-r)^4) (negative)But in the given sequence, the fifth term is (-4), which is negative, but the second and fourth terms would be positive, which is not specified in the problem. So, to keep all terms negative except possibly the second and fourth, but since the problem doesn't specify, I think it's safer to assume that (r) is positive because the fifth term is negative, same as the first term.Therefore, (r = sqrt[4]{4}). Let me compute that:(sqrt[4]{4} = (4)^{1/4} = (2^2)^{1/4} = 2^{2/4} = 2^{1/2} = sqrt{2})So, (r = sqrt{2}). Now, let me find (b_{2}):(b_{2} = -1 times r^2 = -1 times (sqrt{2})^2 = -1 times 2 = -2)So, (b_{2} = -2).Now, going back to the original expression I need to find: (dfrac{a_{1}a_{2}}{b_{2}})Substituting the values:(dfrac{2 times 5}{-2} = dfrac{10}{-2} = -5)So, the value is (-5), which corresponds to option A.Wait, let me double-check my steps to make sure I didn't make any mistakes.1. Arithmetic sequence: - Common difference (d = 3) - (a_{1} = 2), (a_{2} = 5) - Seems correct.2. Geometric sequence: - Common ratio (r = sqrt{2}) - (b_{2} = -2) - Seems correct.3. Calculation: - (dfrac{2 times 5}{-2} = -5) - Correct.I think everything checks out. So, the answer should be A: (-5).**Final Answer**boxed{A}
❓The length of the bridge, which a train 110 meters long and traveling at 45 km/hr can cross in 30 seconds, is?
💡First, I need to determine the length of the bridge that the train crosses. The train is 110 meters long and travels at a speed of 45 kilometers per hour. It takes the train 30 seconds to completely cross the bridge.To make the units consistent, I'll convert the train's speed from kilometers per hour to meters per second. There are 1000 meters in a kilometer and 3600 seconds in an hour, so:45 km/hr = (45 × 1000) / 3600 = 12.5 m/sNow, the train's speed is 12.5 meters per second. The total distance the train travels while crossing the bridge is the sum of the train's length and the bridge's length. Let's denote the bridge's length as L.The total distance can be calculated by multiplying the speed by the time:Total distance = Speed × Time = 12.5 m/s × 30 s = 375 metersSince the total distance is the sum of the train's length and the bridge's length:375 meters = 110 meters + LSolving for L:L = 375 meters - 110 meters = 265 metersTherefore, the length of the bridge is 265 meters.
❓At the end of the cave, they found a golden chest. The chest contains some diamonds and 377 rubies. There are 44 more diamonds than rubies. How many diamonds are in the chest?
💡First, identify the number of rubies, which is given as 377.Next, understand that there are 44 more diamonds than rubies.To find the number of diamonds, add 44 to the number of rubies: 377 + 44 = 421.Therefore, there are 421 diamonds in the chest.
❓Given proposition p: The graph of the function y=a^{x+1}+1 (where a>0 and aneq 1) always passes through the point (-1, 2); proposition q: Given that plane alpha is parallel to plane beta, then the condition that line m is parallel to alpha is the necessary and sufficient condition for line m to be parallel to beta; among the following propositions, the true one is ( )A: p land qB: lnot p land lnot qC: lnot p land qD: p land lnot q
💡Okay, so I have this problem with two propositions, p and q, and I need to figure out which combination of them is true. The options are A: p ∧ q, B: ¬p ∧ ¬q, C: ¬p ∧ q, and D: p ∧ ¬q. Let me take it step by step.Starting with proposition p: "The graph of the function y = a^{x+1} + 1 (where a > 0 and a ≠ 1) always passes through the point (-1, 2)." Hmm, okay, so I need to check if when x is -1, y is indeed 2. Let me plug in x = -1 into the function.So, y = a^{-1 + 1} + 1 = a^{0} + 1. Since any number to the power of 0 is 1, this simplifies to y = 1 + 1 = 2. So, regardless of the value of a (as long as a > 0 and a ≠ 1), the point (-1, 2) will always be on the graph. That means proposition p is true.Alright, moving on to proposition q: "Given that plane α is parallel to plane β, then the condition that line m is parallel to α is the necessary and sufficient condition for line m to be parallel to β." Hmm, this one is a bit trickier. Let me break it down.First, if two planes α and β are parallel, then any line that is parallel to α should also be parallel to β, right? Because if a line is parallel to one plane, it shouldn't intersect it, and since the planes are parallel, it shouldn't intersect the other plane either. So, does that make the condition both necessary and sufficient?Wait, let me think again. If line m is parallel to α, does that necessarily mean it's parallel to β? Since α and β are parallel, yes, because the direction of the line doesn't change relative to the other plane. So, it's sufficient. But is it necessary? That is, if line m is parallel to β, does it have to be parallel to α?Hmm, if a line is parallel to β, since α and β are parallel, the line should also be parallel to α. So, it seems like the condition is both necessary and sufficient. But wait, is there a case where a line could be parallel to β but not to α? I don't think so because the planes are parallel, so their orientations are the same. Therefore, any line parallel to one should be parallel to the other.Wait, but hold on. What if the line is lying on plane α? Then it's not parallel to α, but if α is parallel to β, the line would still be parallel to β because it doesn't intersect β. So, in that case, the line is not parallel to α, but it's parallel to β. That means the condition that line m is parallel to α is not necessary for it to be parallel to β. Because the line could be on α and still be parallel to β.So, that means the condition is sufficient but not necessary. Therefore, proposition q is false because it claims that the condition is both necessary and sufficient, but it's only sufficient.Wait, let me clarify. If line m is parallel to α, then it's parallel to β—that's the sufficient part. But if line m is parallel to β, it doesn't necessarily mean it's parallel to α because it could be lying on α. So, the condition is sufficient but not necessary. Therefore, the statement in q is incorrect because it says it's a necessary and sufficient condition, but it's only sufficient. So, q is false.So, summarizing: p is true, q is false. Therefore, the correct combination is p ∧ ¬q, which is option D.**Final Answer**boxed{D}
❓If you toss a fair coin 4 times in a row, the probability that the number of heads is greater than the number of tails is ( ).A: ( dfrac{1}{4} )B: ( dfrac{3}{8} )C: ( dfrac{1}{2} )D: ( dfrac{5}{16} )
💡Okay, so I have this probability problem here: If I toss a fair coin 4 times in a row, what's the probability that the number of heads is greater than the number of tails? The options are A: 1/4, B: 3/8, C: 1/2, and D: 5/16.Alright, let's break this down. First, I know that when dealing with coins, each toss is independent, and the probability of getting heads or tails is equal, which is 1/2 for each. Since we're tossing the coin 4 times, there are a total number of possible outcomes. I think that's calculated by 2^4, which is 16. So, there are 16 possible different outcomes when tossing a coin 4 times.Now, the question is asking for the probability that the number of heads is greater than the number of tails. So, in 4 tosses, how many heads do we need for that to happen? Well, if we have more heads than tails, that means we need at least 3 heads, right? Because if we have 2 heads and 2 tails, they're equal, and if we have 1 head and 3 tails, there are more tails. So, to have more heads, we need either 3 heads and 1 tail or 4 heads and 0 tails.Okay, so we need to calculate the probability of getting exactly 3 heads and exactly 4 heads, and then add those probabilities together.To find the probability of getting exactly 3 heads out of 4 tosses, I think we can use the combination formula. The formula for the probability of getting exactly k successes (in this case, heads) in n trials is given by the binomial probability formula:P(k) = C(n, k) * p^k * (1-p)^(n-k)Where C(n, k) is the combination of n things taken k at a time, p is the probability of success on a single trial, and (1-p) is the probability of failure.Since the coin is fair, p = 1/2 for heads and (1-p) = 1/2 for tails.So, for exactly 3 heads:C(4, 3) * (1/2)^3 * (1/2)^(4-3)C(4, 3) is the number of ways to choose 3 successes out of 4 trials. I remember that C(n, k) is calculated as n! / (k!(n-k)!).So, C(4, 3) = 4! / (3! * (4-3)!) = (4*3*2*1) / ((3*2*1)*(1)) = 24 / (6*1) = 4.So, C(4, 3) is 4.Then, (1/2)^3 = 1/8, and (1/2)^1 = 1/2.Multiplying them together: 4 * (1/8) * (1/2) = 4 * (1/16) = 4/16 = 1/4.Okay, so the probability of getting exactly 3 heads is 1/4.Now, for exactly 4 heads:C(4, 4) * (1/2)^4 * (1/2)^(4-4)C(4, 4) is the number of ways to choose all 4 successes out of 4 trials. That should be 1, since there's only one way to get all heads.So, C(4, 4) = 1.(1/2)^4 = 1/16, and (1/2)^0 = 1, since anything raised to the power of 0 is 1.Multiplying them together: 1 * (1/16) * 1 = 1/16.So, the probability of getting exactly 4 heads is 1/16.Now, to find the total probability of getting more heads than tails, we add the probabilities of getting exactly 3 heads and exactly 4 heads.So, total probability = 1/4 + 1/16.To add these fractions, they need a common denominator. The denominators are 4 and 16, so the common denominator is 16.1/4 is equivalent to 4/16.So, 4/16 + 1/16 = 5/16.Therefore, the probability of getting more heads than tails when tossing a fair coin 4 times is 5/16.Looking back at the options, D is 5/16, so that should be the correct answer.Wait, just to make sure I didn't make any mistakes, let me double-check my calculations.First, total possible outcomes: 2^4 = 16. That seems right.Number of ways to get exactly 3 heads: C(4,3) = 4. That makes sense because there are 4 different positions where the single tail could occur.Probability for each of those is (1/2)^4 = 1/16. So, 4 * 1/16 = 4/16 = 1/4. That checks out.Number of ways to get exactly 4 heads: C(4,4) = 1. Only one way, all heads.Probability is (1/2)^4 = 1/16.Adding them: 1/4 + 1/16 = 5/16. Yep, that seems correct.I think I'm confident that D: 5/16 is the right answer.
❓Find the range of the constant k such that the simultaneous equationsbegin{align*}3x - 2y &= 7, kx + 4y &= 10,end{align*}have a solution (x, y) in Quadrant I.A. k > -6B. k < frac{30}{7}C. -6 < k < frac{30}{7}D. -6 leq k leq frac{30}{7}
💡Okay, so I have this problem here with two equations:3x - 2y = 7andkx + 4y = 10And I need to find the range of the constant k such that the solution (x, y) lies in Quadrant I. Hmm, Quadrant I means both x and y have to be positive. So, I need to solve these equations and then figure out the conditions on k that make both x and y positive.Alright, let's start by solving the system of equations. I can use either substitution or elimination. Maybe substitution is easier here. Let me solve the first equation for one of the variables. Let's solve for y.From the first equation:3x - 2y = 7Subtract 3x from both sides:-2y = -3x + 7Divide both sides by -2:y = (3x - 7)/2Okay, so y is expressed in terms of x. Now, let's plug this expression for y into the second equation.The second equation is:kx + 4y = 10Substitute y:kx + 4*( (3x - 7)/2 ) = 10Simplify the 4 and the denominator 2:kx + 2*(3x - 7) = 10Multiply out the 2:kx + 6x - 14 = 10Combine like terms:(k + 6)x - 14 = 10Add 14 to both sides:(k + 6)x = 24Now, solve for x:x = 24 / (k + 6)Okay, so x is 24 divided by (k + 6). Now, since we need x to be positive (because we're in Quadrant I), the denominator (k + 6) must be positive. So:k + 6 > 0Which implies:k > -6Alright, so that's one condition. Now, let's find y in terms of k. Earlier, we had y = (3x - 7)/2. Let's substitute x = 24 / (k + 6) into this.y = (3*(24 / (k + 6)) - 7)/2Simplify numerator:First, compute 3*(24 / (k + 6)):72 / (k + 6)Then subtract 7:72 / (k + 6) - 7To combine these, write 7 as 7*(k + 6)/(k + 6):72 / (k + 6) - 7*(k + 6)/(k + 6) = (72 - 7k - 42) / (k + 6)Simplify numerator:72 - 42 = 30, so:(30 - 7k) / (k + 6)Now, divide by 2:y = (30 - 7k) / [2*(k + 6)]So, y is (30 - 7k) divided by [2*(k + 6)]. Since y must also be positive, the numerator and denominator must have the same sign. We already know from x that (k + 6) is positive, so the numerator must also be positive:30 - 7k > 0Solve for k:30 > 7kDivide both sides by 7:30/7 > kWhich is the same as:k < 30/7So, combining both conditions:k > -6 and k < 30/7So, the range of k is:-6 < k < 30/7Let me just double-check to make sure I didn't make any mistakes. So, solving for x, I got x = 24/(k + 6). For x to be positive, k + 6 must be positive, so k > -6. Then, for y, I substituted x into the expression for y and simplified to get y = (30 - 7k)/(2*(k + 6)). Since (k + 6) is positive, the numerator must also be positive, so 30 - 7k > 0, which gives k < 30/7. So, yes, combining these, k must be greater than -6 and less than 30/7.I think that makes sense. So, the correct answer should be option C: -6 < k < 30/7.**Final Answer**boxed{C}